KEPRIBADIAN GURU DALAM DUNIA PENDIDIKAN - Asril Sa'ad Nasution; Azizul Makris (JURNAL MUMTAZ, 2022)
The teacher is a profession in education who have ups and downs, the teachers considered sacred profession and proud. This was seen when proudly bermenantukan a teacher. However, this time the teacher allegedly as a profession marginalized. It is evident from the many generations that little aspire to be a teacher, because the teacher does not have a large income, such as doctors, engineers, pilots and so forth. Teacher taught his students that are beneficial and useful knowledge for the benefit of mankind, teacher personality has its own advantages. However, there are those who say the teacher's personality is difficultto find the levels and not easy to find the limit and it is also hard to be defined thoroughly.